(untitled) (Medical Forum Monthly, 2022)
Objective: To assess the nutritional status of the senior citizens of 60 years age and above and to determine the factors affecting the nutritional status of the senior citizens of 60 years age and above. Study Design: Descriptive Cross Sectional Study Place and Duration of Study: This study was conducted at the Department of Community Medicine, Sialkot Medical College, Sialkot from March 2020 to September, 2020. Materials and Methods: Two hundred senior citizens aged sixty years and above living in Sialkot were interviewed through a questionnaire, using anthropometric measurements, 24-hours recall and clinical examination. Results: The nutritional status of the elderly living in the joint family system and having some source of income was better than those who were jobless and living in the nuclear family system. Average calories intake per day by males was 2325 and 2175 in females. The average protein intake per day was 49 gm by males and 44 gm in females. These values are less than the recently calculated national values of 60 gm by Pakistan Economic Survey 2019-20. The average intake of caloric consumption calculated for the respondents were well below the National Recommended Daily Allowance1. Conclusion: The study revealed that the respondents with joint family system get better nutritional care and social support. Since work participation in Pakistan is predominantly by male, financial contribution is much higher by elderly males rather than elderly females.